Addie Model-Based Learning To Improve Competences Of Clinical Nurse Leaders - Djojo, Achmad; Suhariyanto, S; Kapadia, Raju; Octary, Tiara; Junaidi, J; Sari, Delsy Cantika; Fitriadi, Khairul; Merry, Maria; Lestari, Astuti; Nilaprapti, Endang; Rosyada, Ida; Yudi, Yudi; Novita, Irawati; Nandang, Ignatius; Rachmadi, Agus; Hariyati, Tutik Sri; Handiyani, Hanny (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Introduction: Clinical nurse leaders (CNL) play a significant role in improving the quality of nursing services. Such a role includes satisfying clients during the care process by referring to the nursing goal. In meeting the standard, CNL should enhance their knowledge, attitude, and soft and hard skills. Purpose: Identifying the competences of CNL through ADDIE model-based learning. Method: The present study relied on a pre-experimental design with a one-group pre-test and post-test.This study used quantitative research with the pre experiment method, and pre and post test.As many as 20 clinical nurse leaders from inpatient units of accredited public and private hospitals in Singkawang were involved as the sample. Further, the data analysis in this study used Paired T test. The result of this study found a meaningfulimprovement of competences among CNL through ADDIE model-based learning (p=.006). Recommendation: ADDIE model-based learning attempts to enhance the competences of CNL. This research recommends the addition of the ADDIE model to advance the competence as the clinical nurse leaders.  Moreover, this strategy can be applied to develop CNL’s ability in other managerial fields.